(untitled) (Altre Modernità, 2013)
The remains of the Mayan civilization describe (among other things) many observations of various astronomical phenomena observed by the Maya. The modern Celestial Mechanics allows us to calculate with great accuracy when astronomical phenomena occurred and were visible in the sky for a given location on Earth too far back in time. The Maya developed the very accurate calendar known as the Long Count, but when we want to synchronize it with the western one, the correlation between the two is surprisingly very uncertain. The two calendars can be connected each other by analyzing historical data and various astronomical phenomena of which we have a paper trail in the ancient texts that is sufficient to establish an appropriate chronology. The correlation between the Long Count and the Gregorian calendar has been studied by many authors who have obtained correlation values very different from each other (almost 50 different values), which differ from one another by hundreds of years, producing considerable uncertainty in Mayan history in relation to other civilizations. Astronomy can potentially solve the problem of the correct identification of the relationship, provided that the records are available from the observations performed and documented chronologically according to the Mayan Long Count. In the present work has been performed the statistical analysis of the 52 correlations at present known and used pointing out that at the present state of knowledge it is not possible to get the exact determination of the coefficient of synchronization (correlation) between the Long Count and the Western calendar, but only an assessment of its probability distribution function, thus allowing you to assign a probability value to each value of the correlation that has been published. The statistical analysis of the 52 values at present known leads to an optimal value of the correlation constant of JDN 588159 with an uncertainty of about ±35 years.